Factors Affecting Turnover Intention: A Literature Review - Nilhar Apriani; Zulkifli Musannip Efendi Siregar (Garuda Prestasi Nusantara Consulting, 2023)
There are many things that become the question why an employee leaves the organization or company where he works. This action is called turnover intention, namely the tendency or intention of employees to quit their job. Of course, this is an important issue for companies to find out the cause because employee turnover requires a large amount of money. The purpose of this literature review is to identify the factors that influence turnover intention. Methods Writing articles use the method of collecting data from literature studies (literature review) of national and international journals about employee turnover intentions. Article searches were carried out on the Google Scholar database using keywords. There were 15 articles reviewed. The results of the literature review conducted showed that there are many factors that influence turnover intention. Factors that trigger turnover intentions include aspects of work, job satisfaction, work stress, age, education level, work culture, work pressure, workload, marital status and job insecurity. Then the factors that can reduce turnover intentions are good leadership, internal and external work environment, high organizational commitment and low role conflict. Keywords: Turnover Intention, Turnover Intention Factor